ACHIEVEMENTS OF MC MARY KOM AN OLYMPIAN OF MANIPUR: A CASE STUDY - Longjam, Nilakanta; L. Pungding (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study's title was "The Achievements of MC Mary Kom an olympian of Manipur: A Case Study." A case study (or a case report) is an intensive analysis of an individual unit (e.g., a person, group, or event) stressing context-related developmental factors. The study's objective was to study the achievements of MC Mary Kom. The study leaves aside the lower level of achievements obtained by MC Mary Kom. It studies only National and International achievements obtained by MC Mary Kom. Data for this investigation was derived from primary and secondary sources. Primary sources include interviews, family members, and official and personal records. Secondary sources include newspapers, magazines, and media, which carry information about the achievements of MC Mary Kom in National and International.